2017
DOI: 10.1111/gcb.13781
|View full text |Cite
|
Sign up to set email alerts
|

Changes in temperature sensitivity of spring phenology with recent climate warming in Switzerland are related to shifts of the preseason

Abstract: The spring phenology of plants in temperate regions strongly responds to spring temperatures. Climate warming has caused substantial phenological advances in the past, but trends to be expected in the future are uncertain. A simple indicator is temperature sensitivity, the phenological advance statistically associated with a 1°C warmer mean temperature during the "preseason", defined as the most temperature-sensitive period preceding the phenological event. Recent analyses of phenological records have shown a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 63 publications
6
86
2
1
Order By: Relevance
“…We tested this hypothesis by applying four chilling-based models for 2080-2099 but kept the winter temperature (S3) or the spring temperature (S4) constant and then assessing their difference to simulations based on varying winter and spring temperatures (S5; Figures S10a-S10h; see section 2). Experimental studies comparing phenology in regions at lower and higher elevations have reported similar findings (Gusewell et al, 2017;Vitasse et al, 2018). The predicted SOSs across most of the NH (mainly at higher latitudes) did not differ significantly between these two simulations (p > 0.05).…”
Section: Determinations Of the Increasing Synchrony Of Spring Phenologysupporting
confidence: 56%
“…We tested this hypothesis by applying four chilling-based models for 2080-2099 but kept the winter temperature (S3) or the spring temperature (S4) constant and then assessing their difference to simulations based on varying winter and spring temperatures (S5; Figures S10a-S10h; see section 2). Experimental studies comparing phenology in regions at lower and higher elevations have reported similar findings (Gusewell et al, 2017;Vitasse et al, 2018). The predicted SOSs across most of the NH (mainly at higher latitudes) did not differ significantly between these two simulations (p > 0.05).…”
Section: Determinations Of the Increasing Synchrony Of Spring Phenologysupporting
confidence: 56%
“…Despite the wider range of spring temperature anomalies at cold sites (3.2 °C vs. 2.9 °C in warm sites), we observed less variability in the timing of green‐up (7.8 days in cold sites vs. 9.8 days in warm sites). Our findings do not necessarily contradict previous studies finding higher photoperiod sensitivity in lower latitudes (Zohner et al, ), as higher temperature sensitivity and higher photoperiod sensitivity could co‐occur and photoperiod limitation may not explain spatial patterns of temperature sensitivity of green‐up (Güsewell et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was not the aim of our paper to disentangle the contribution of the obvious reasons for this result, but the moving window approach clearly showed that spring and winter warming trends exhibited very similar variation overtime, that is, the strongest trends in the 1980-2010 period. Thus, it is more likely that a reduction in forcing conditions has driven the decrease in the advance of spring and summer phenology (as reported by Güsewell et al, 2017 for Switzerland) than a lack of chilling (e.g. .…”
Section: Attribution Of Phenological Changes To Warmingmentioning
confidence: 91%
“…However, there are also contrasting opinions for example, by Wang et al (). Güsewell, Furrer, Gehrig, and Pietragalla () showed that for Switzerland there are still no indications of a lack of chilling leading to altered temperature sensitivities. Changes in temperature sensitivities are reported as not uniform over time (Chen et al, ) and, in particular, a weakened temperature response was observed since 2000 (Fu et al, ).…”
Section: Introductionmentioning
confidence: 99%